The Association between Outside Directors, Institutional Investors and the Properties of Management Earnings Forecasts - AJINKYA, BIPIN; BHOJRAJ, SANJEEV; SENGUPTA, PARTHA (Journal of Accounting Research, 2005)
We investigate the relation of the board of directors and institutional ownership with the properties of management earnings forecasts. We find that firms with more outside directors and greater institutional ownership are more likely to issue a forecast and are inclined to forecast more frequently. In addition, these forecasts tend to be more specific, accurate and less optimistically biased. These results are robust to changes specification, Granger causality tests, and simultaneous equation analyses. The results are similar in the pre– and post–Regulation Fair Disclosure (Reg FD) eras. Additional analysis suggests that concentrated institutional ownership is negatively associated with forecast properties. This association is less negative in the post–Reg FD environment, which is consistent with Reg FD reducing the ability of firms to privately communicate information to select audiences.